Development of a novel, high-affinity ssDNA trypsin inhibitor - Stanislaw Malicki; Miroslaw Ksiazek; Pawel Majewski; Aleksandra Pecak; Piotr Mydel; Przemyslaw Grudnik; Grzegorz Dubin (Journal of Enzyme Inhibition and Medicinal Chemistry, 2019)
Inhibitors of serine proteases are not only extremely useful in the basic research but are also applied extensively in clinical settings. Using Systematic Evolution of Ligands by Exponential Enrichment (SELEX) approach we developed a family of novel, single-stranded DNA aptamers capable of specific trypsin inhibition. Our most potent candidate (T24) and its short version (T59) were thoroughly characterised in terms of efficacy. T24 and T59 efficiently inhibited bovine trypsin with Ki of 176 nM and 475 nM, respectively. Interestingly, in contrast to the majority of known trypsin inhibitors, the selected aptamers have superior specificity and did not interact with porcine trypsin or any human proteases tested. These included plasmin and thrombin characterised by trypsin-like substrate specificity. Our results demonstrate that SELEX may be successfully employed in the development of potent and specific DNA based protease inhibitors.